PETA PERKEMBANGAN BIDANG ENERGI BERDASARKAN LITERATUR KELABU DI INDONESIA - Hartinah, Sri; Tupan, Tupan; Iswanti, Setya; Rahartri, Rahartri; Prahastut, S. (BACA: Jurnal Dokumentasi dan Informasi, 2009)
The Objective of this study is to analyze the subject research in order to construct a map of energy research conducted by R & D Institutions and university student in Indonesia. The method of the study uses Bibliometrics by collecting the data from 1998-2008. The data analyze throughout document mapping in co-word. The data result in energy sector that carried out by the R & D Institutions and the university is: 328 titles of thesis and 345 titles of research reports. Based on the collected data, there is a significant increasing in the research development from 1998 until 2008, except in 1999 which decrease from 1998 and 2004 decrease from 2003. The title numbers of university thesis from the highest are ITB, ITS, UGM, UNIBRAW, UI, UNSRI, USU, and another collections from other university are from PDII-LIPI. The title numbers of research institute are: Department of ESDM, LIPI, BATAN, KRT, and LAPAN. The research are focused on: biofuel, electricity energy, solar energy, coals, fuel energy, nuclear energy, wind energy, petroleum and natural gas, geothermal energy, bio mass and biogas, sea current and sea wave, steam energy, and hydrogen/fuel cell, whereas under the 10 research titles there are a lot of kinds of energy such as gas, earth gas, steam, and alternative energies, and others focuses. This study concludes that there are 46 topics which conducted research by university as well as R & D Institutions. The output of this study is database, containing of 960 records of energy research. The result shows the differences of mapping for energy research. This research recommends the need of documentation system policy on grey literature especially on energy research.